Heroism or Capitulation? A Reassessment of Salah al-Din, the Battle of Arsuf (1191 CE) and the al-Ramla Treaty (1192 CE) - Abu-Munshar, Maher Y. (Journal of Al-Tamaddun, 2025)
The Treaty of al-Ramla, signed on 2 September 1192, formally brought the Third Crusade (1189-1192) to a close. Spearheaded by prominent European monarchs -most notably Richard I of England- the Crusade was waged against Sultan Salah al-Din al-Ayyubi (1137-1193), the preeminent Muslim ruler and strategic commander of the era. While the swords of both figures illuminated during the years of that Crusade, the treaty itself was executed not by their own pens, but through their appointed representatives. This accord represents a pivotal juncture in the annals of Crusading history, distinguished not only by its terms but also by the protracted diplomatic engagements between Crusader and Muslim envoys that preceded it. Despite Salah al-Din’s considerable military and political exertions -especially his pivotal liberation of Jerusalem in 1187 and the campaigns that followed until the al-Ramla treaty- a recent polemical opinion by Egyptian writer Dr Yusuf Zaidan casts the Sultan as “one of the most despicable figures in human history.” Zaidan’s opinion starkly contrasts with prevailing historical narratives. He attributes al-Ramla treaty to Salah al-Din’s alleged weakness and negligence claiming it was just the climax of his setbacks and a clear indication of his weakness in front of King Richard. He contends that, notwithstanding the retaining of sovereignty over Jerusalem, the concessions made to the Crusaders across other regions of Palestine and Bilad al-Sham epitomise a capitulation rather than a strategic triumph. This study undertakes a comprehensive examination of the al-Ramla Peace Treaty, interrogating the underlying strategic rationales which compelled both parties to deem peace the only tenable option at that juncture. It further scrutinises the implications of the Battle of Arsuf (1191) alongside internal Crusader discord, to evaluate whether the treaty constitutes the pinnacle of Salah al-Din’s victories or, conversely, as Zaidan claims, the end of his setbacks.